DEVELOPMENT OF E-LKPD BIOTECHNOLOGY TOPIC INTREGRATED WITH LOCAL WISDOM BASED ON SCIENTIFIC APPROACH - Cici Wahyuni; Yurnetti Yurnetti (Universe, 2023)
E-LKPD biotechnology topic intregrated with local wisdom based on scientific approach has been developed and analyzed the validity and practicality to assist the learning process. This research classified to research and development (R&D) using the ADDIE model. This research is limited to the development stage only. Research instrument used consisted of validity and practicality questionnaires. The subjects of this study were three lecturers of the Science Education department as validators, three science teachers as practicalists and six students of class IX of SMP Negeri 39 Padang as practicalists. The data in this study are primary data obtained from the results of validation and practicality questionnaires. Data were analyzed using Cohen's kappa formula. The results of the validity test of the E-LKPD obtained a value of 0.86 with a very high validity category in terms of aspects of the feasibility of content, language, presentation and graphics. The results of the E-LKPD practicality test were obtained from the teacher's response of 0.95 with a very high practicality category while the E-LKPD practicality test value obtained from the student responses was 0.82 with a very high practicality category in terms of ease of use, efficiency of learning time , and benefits